Peran Pengetahuan Pajak, Sanksi Pajak dan Insentif Pajak terhadap Kepatuhan Wajib Pajak Dengan Teknologi Informasi Sebagai Variabel Moderasi - Richard; Hexana Sri Lastanti (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The aim of this research is to examine the influence of tax knowledge, tax sanctions, and tax incentives on taxpayer compliance, moderated by information technology. This study employs a quantitative approach. The sample for this research consists of 180 respondents from MSMEs in the culinary, trade, automotive, industry, and service sectors. The research data was obtained through the distribution of questionnaires and analyzed using SEM PLS analysis techniques.The results of this study indicate that tax knowledge, tax sanctions, and tax incentives all have a positive and significant impact on taxpayer compliance. However, the role of information technology in moderating this influence varies. High tax knowledge and strict tax sanctions consistently increase taxpayer compliance across various studies, while clear and effective tax incentives also encourage compliance. The findings show that information technology can moderate the effect of tax sanctions by enhancing the efficiency and transparency of tax law enforcement, helping taxpayers understand and comply with their obligations better. However, the moderating role of information technology on the influence of tax knowledge and tax incentives on taxpayer compliance is not significant. This may be due to challenges such as low digital literacy, limited access to technology, system complexity, and resistance to change.